DEVELOPMENT OF HR OPERATIONAL DASHBOARD WEBSITE AT PT. TELKOM REGIONAL VI - Muhammad Gilvy Langgawan Putra; Muhammad Iqbal Firdaus; Nurvianto Samputra Makruf; Aidil Saputra Kirsan (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2023)
Human resources are a very valuable asset in a company where these resources are employees. Human Resources (HR) department is part of a company in charge of managing employees. HR managers have an important role to present data and workforce profiles, understand company needs, and provide recommendations regarding employee management to improve company performance. PT Telkom Indonesia (Persero) Tbk (Telkom) is a State-Owned Enterprise (BUMN) that is in the field of information and communication technology (ICT) services and telecommunication networks in Indonesia. PT Telkom Regional VI is a part of PT Telkom which operates in the Borneo area. In daily operational activities, HR managers are asked to present a workforce profile. To present data, HR managers need to collect data from various sources. Due to different data sources, management has difficulty in reading labor data so that it can trigger a revision of data presentation. Repeating management of similar data also causes additional allocation of time and effort. Therefore, this study aims to develop the HR Operational Dashboard Website at PT Telkom Regional VI using the scrum model. The stages in the scrum include sprint planning, daily scrum, sprint review, and sprint retrospective. The HR Operational Dashboard website was successfully developed using the scrum method with a total product backlog of 27 items in 6 sprints. This website can help HR manager presents accurate data and can be a media to support decision-making.